2013
DOI: 10.1080/02185385.2013.793019
|View full text |Cite
|
Sign up to set email alerts
|

Does job satisfaction mediate the relationship between work–family conflict and psychological strain? A study of Australian social workers

Abstract: The present study investigated the mediating effects of job satisfaction on the relationship between work-family conflict and psychological strain among Australian social workers. Data for the study were collected by an online survey of the membership of the Australian Association of Social Workers, yielding 439 usable responses. The results provide evidence that job satisfaction mediates the relationship between work-to-family conflict, family-to-work conflict and psychological strain. These findings contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Job satisfaction is influenced by many antecedents, including employee welfare, team atmosphere, and organizational culture [ 31 ]. Past studies have indicated that job satisfaction plays a mediating role in the relationship between many variables, such as the relationship between positive affectivity and work motivation in the context of complex projects [ 32 ], and the relationship between WFC and psychological strain [ 33 ]. In addition, previous research has indicated that job satisfaction moderates the relationship between many variables in the context of a project, such as the relationship between equity and extra-role behaviors [ 34 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Job satisfaction is influenced by many antecedents, including employee welfare, team atmosphere, and organizational culture [ 31 ]. Past studies have indicated that job satisfaction plays a mediating role in the relationship between many variables, such as the relationship between positive affectivity and work motivation in the context of complex projects [ 32 ], and the relationship between WFC and psychological strain [ 33 ]. In addition, previous research has indicated that job satisfaction moderates the relationship between many variables in the context of a project, such as the relationship between equity and extra-role behaviors [ 34 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Work-family conflict has a negative impact on an employee’s work and family life, as well as his/her physical and mental health and well-being [1,2,3,4]. Similarly, work-family conflict leads to higher job stress levels and dissatisfaction levels, which can even lead to resignation [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Given that the work and family role systems represent the two most important domains of life for most people (Grandey, Cordeiro, & Crouter, 2005), an incompatibility between them can have negative impact on nurses' well-being and thereby detract from the quality of care rendered and patient outcomes. Extant research has associated work-family conflict with negative physical health outcomes and health-related behaviours (Allen & Armstrong, 2006;Berkman et al, 2015;van Steenbergen & Ellemers, 2009) as well as psychological outcomes such as anxiety, depression and life satisfaction (Kalliath & Kalliath, 2013;Moen et al, 2015). Work-family conflict also has implications for the quality of work life and retention of nurses.…”
mentioning
confidence: 99%